Analyzing the response distribution of DO concentration and its environmental factors under the influence of typhoon rain events with remote sensing - Shen, Weiping; Jin, Yuhao; Li, Gengying; Cong, Peitong (Frontiers in Ecology and Evolution, 2023)
Typhoon rain events are important factors that trigger changes in dissolved oxygen concentrations in watersheds. The direction of the typhoon driving force is clear, but the mode of action and mechanism are complex. Moreover, quantifying the relationship between these actions and dissolved oxygen is challenging. This study collected measured data from water quality monitoring and remote sensing during the 2022 typhoon rain events. By analyzing the changes in typhoon driving factors and dissolved oxygen (DO) concentrations in water under various typhoon storms, extended MOORA plus the full multiplicative form (MULTIMOORA), Multiscale Geographic Weighted Regression (MGWR), and spatial autocorrelation analysis were used to evaluate the response of DO concentration. Furthermore, the effects of the atmospheric environment under the influence of human activities on the response distribution of the urban water environment were analyzed. The results of the study showed that under the effect of a typhoon with higher rainfall intensity, the response of DO concentration in the water body of the river in the center of the city was better. However, the response of DO concentration in the water body at the mouth of the sea had a tendency to become worse. Under the influence of typhoon rain events with smaller intensity, the scouring effect of rainwater dominated, and the DO concentration response in the water body had a tendency to become worse. The analysis of spatial heterogeneity under the influence of human activities showed that the ranking values of DO concentration response in rivers in the city area of Zhongshan, under the influence of typhoon rain events, were positively correlated with the distribution of ozone (O3O3) concentration and sulfur dioxide (SO2SO2) concentration in the eastern, central, and western parts of Zhongshan. Conversely, it was negatively correlated with the distribution of O3O3 concentration and SO2SO2 concentration in the northern and southern parts of Zhongshan. Based on the research results, we constructed a technique to evaluate the response of dissolved oxygen concentration during the typhoon transit period, which can provide an indicator reference for urban managers in water environment management.